PEMANFAATAN KAHOOT SEBAGAI MEDIA EVALUASI KIMIA DI MASA PEMBELAJARAN TATAP MUKA TERBATAS - LENY CHRISTIANA (TEACHER : Jurnal Inovasi Karya Ilmiah Guru, 2022)
he purpose of writing this literature research article is to find out the use of kahoot as a medium for chemical evaluation in the Limited Face-to-face Learning Period. Research on the publication of this article uses a literature study or literature review method that focuses on the results of writing related to the theme of writing. The data used in this study comes from the results of research that has been carried out and published in national online journals. Based on a literature study or literature review, it shows that the Kahoot application is very suitable for use in the learning process, namely when carrying out evaluations or assessments of chemistry subjects during Limited Face-to-face Learning. This is because using the Kahoot application can improve student learning outcomes, improve thinking skills, and student interests. This is because the Kahoot application can be used as a learning evaluation medium in the form of interactive quizzes that are very effective, fun, and make students more enthusiastic in learning. Learning evaluations can be given to students as assignments, quizzes, daily assessments, mid-semester assessments, or end-of-semester assessments. The Kahoot application is an online interactive game, where one of the obstacles it faces is the stability of the internet network from providers in each region. So that online evaluation using Kahoot will be optimal if the internet network is stable, as well as the readiness of educators and students to use it in teaching and learning activities. ABSTRAKTujuan penulisan artikel penelitian literatur ini adalah untuk mengetahui pemanfaatan kahoot sebagai media evaluasi kimia di Masa Pembelajaran Tatap Muka Terbatas. Penelitian pada pebulisan artikel ini menggunakan metode studi kepustakaan atau literature review yang berfokus pada hasil penulisan yang berkaitan dengan tema penulisan. Data yang digunakan dalam penelitian ini berasal dari hasil-hasil penelitian yang sudah dilakukan dan diterbitkan jurnal online nasional. Berdasarkan studi kepustakaan atau literature review menunjukkan bahwa aplikasi Kahoot sangat layak digunakan dalam proses pembelajaran, yaitu ketika melaksanakan evaluasi atau penilaian mata pelajaran kimia pada saat Pembelajaran Tatap Muka Terbatas. Hal ini dikarenakan dengan menggunakan aplikasi Kahoot dapat meningkatkan hasil belajar peserta didik, meningkatkan kemampuan berpikir, dan minat peserta didik. Hal ini karena aplikasi Kahoot dapat digunakan sebagai media evaluasi pembelajaran berupa kuis interaktif yang sangat efektif, menyenangkan, dan membuat peserta didik lebih bersemangat dalam pembelajaran belajar. Evaluasi pembelajaran dapat diberikan kepada peserta didik sebagai tugas, kuis, penilaian harian, penilaian tengah semester, maupun penilaian akhir semester. Aplikasi kahoot merupakan game interaktif online, dimana alah satu kendala yang dihadapinya adalah kestabilan jaringan internet dari provider di setiap wilayah. Sehingga evaluasi online menggunakan kahoot akan optimal jika jaringan internet stabil, serta kesiapan pendidik dan peserta didik dalam penggunaannya pada kegiatan belajar mengajar.